Metode dan Pemahaman Pada Aplikasi Terjemahan Al-Qur’an di Indonesia-Malaysia Dalam Kasus Kebebasan Beragama - Muhammad Alwi HS; Fadhilah Nur Khaerati (Kopertais Wilayah XV Lampung, 2023)
This article discusses methods of translating the Qur'an in the application form, particularly in Indonesia and Malaysia. The five applications from each country consist of one official application and four applications that were randomly selected, with a focus on Surah Al-Kafirun, Surah Al-Baqarah: 256, Surah Yunus: 99, and Surah Al-Qashash: 56. To analyze these various applications, this article uses translation methods of harfiyah and tafsiriyah. This article concludes that the Indonesian and Malaysian Qur’an translation applications present a variety of distinctive methods. Although the Indonesian Qur'an translation application is dominated by tafsiriyah translations, still leaves the dominant harfiyah translation found in the Surah Al-Kafirun. This is different from the Malaysian Qur’an translation application where all the verses and surah are translated by the tafsiriyah method. The tafsiriyah translation of the application version in Indonesia tends to be short compared to the tafsiriyah translation of the Malaysian application version which tends to be long. Regarding their understanding, both of them present the issue of religious freedom from different perspectives. Indonesia refers to the issue of freedom for non-Muslims and is general in nature, while Malaysia refers to the issue of freedom of religion for Muslims and is specific to the case of the Prophet Muhammad. Thus, it can be said that the issue of religious freedom in the context of the state today is more visible in the Indonesian version of the Qur'an translation application.